Preparation and physicochemical characterization of spray-dried and jet-milled microparticles containing bosentan hydrate for dry powder inhalation aerosols - Lee H; Kang J; Lee H; Kim D; Rhee Y; Kim J; Park E; Park C (Dove Medical Press, 2016)
Hyo-Jung Lee,1 Ji-Hyun Kang,1 Hong-Goo Lee,1 Dong-Wook Kim,2 Yun-Seok Rhee,3 Ju-Young Kim,4 Eun-Seok Park,5 Chun-Woong Park1 1College of Pharmacy, Chungbuk National University, 2Department of Pharmaceutical Engineering, Cheongju University, Cheongju, 3College of Pharmacy and Research Institute of Pharmaceutical Sciences, Gyeongsang National University, Jinju, 4College of Pharmacy, Woosuk University, Wanju-gun, 5School of Pharmacy, Sungkyunkwan University, Suwon, Republic of Korea Abstract: The objectives of this study were to prepare bosentan hydrate (BST) microparticles as dry powder inhalations (DPIs) via spray drying and jet milling under various parameters, to comprehensively characterize the physicochemical properties of the BST hydrate microparticles, and to evaluate the aerosol dispersion performance and dissolution behavior as DPIs. The BST microparticles were successfully prepared for DPIs by spray drying from feeding solution concentrations of 1%, 3%, and 5% (w/v) and by jet milling at grinding pressures of 2, 3, and 4 MPa. The physicochemical properties of the spray-dried (SD) and jet-milled (JM) microparticles were determined via scanning electron microscopy, atomic force microscopy, dynamic light scattering particle size analysis, Karl Fischer titration, surface analysis, pycnometry, differential scanning calorimetry, powder X-ray diffraction, and Fourier transform infrared spectroscopy. The in vitro aerosol dispersion performance and drug dissolution behavior were evaluated using an Anderson cascade impactor and a Franz diffusion cell, respectively. The JM microparticles exhibited an irregular corrugated surface and a crystalline solid state, while the SD microparticles were spherical with a smooth surface and an amorphous solid state. Thus, the in vitro aerosol dispersion performance and dissolution behavior as DPIs were considerably different due to the differences in the physicochemical properties of the SD and JM microparticles. In particular, the highest grinding pressures under jet milling exhibited excellent aerosol dispersion performance with statistically higher values of 56.8%±2.0% of respirable fraction and 33.8%±2.3% of fine particle fraction and lower mass median aerodynamic diameter of 5.0±0.3 µm than the others (P<0.05, analysis of variance/Tukey). The drug dissolution mechanism was also affected by the physicochemical properties that determine the dissolution kinetics of the SD and JM microparticles, which were well fitted into the Higuchi and zero-order models, respectively. Keywords: bosentan, dry powder inhalations, pulmonary arterial hypertension, respiratory drug delivery, spray drying, jet milling